POLA HUBUNGAN SOSIAL ANAK BERPRESTASI - Riska Elfira (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2020)
This study aims to describe the relationship patterns of parents, teachers, and peers in supporting children's achievement abilities in mathematics, Indonesian, and science subjects. This research is qualitative, the data method used the method of observation, interviews, and documentation. Checking the credibility of the data using triangulation. Research result; (1) Parents in supporting children's achievements, namely parents as givers of security, parents spend time with children communicating, parents help and control children's activities, parents respect, and respect children with all aspects of their existence. (2) Teachers in supporting children's achievement, namely teachers as controllers of children's activities, provide opportunities for children to learn according to their learning styles, teachers are creative in finding learning approaches, teachers as motivators and accept students as a whole. (3) Peers in supporting children's achievement, namely peers are willing to spend time with them and carry out joint activities, peers provide resources and assistance when needed, peers help children feel that they are children who can do something worthy. warm, trusting, and close relationships with others.